YOGA TRAINING FOR PREGNANT WOMEN TO REDUCE PREGNANCY DISCOMFORT - Fitri Hanriyani, Fitri Hanriyani; Titi Purwitasari Handayani, Titi Purwitasari Handayani; Lina Humaeroh, Lina Humaeroh; Mellysa Wulandari Tasripin, Mellysa Wulandari Tasripin; Annisa Devi Permata, Annisa Devi Permata (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Tarogong Kidul is a sub-district in Garut Regency, West Java Province, the eastern boundary of Garut Kota District, the South of Bayongbong District and Cilawu District, the West of Samarang District, the North of Tarogong Kaler District. Pregnancy is a time when pregnant women experience physiological and psychological changes. Changes that occur during pregnancy can cause complaints or discomfort during pregnancy and result in anxiety in pregnant women. Anxiety in pregnant women can be overcome with one of the complementary therapies, namely relaxing prenatal yoga. The involvement of Karsa Husada Health Institute Garut as one of the stakeholders in the pregnant mother class is intended to enable them to actively participate in the program to reduce anxiety in pregnant women. This activity for STIKes Karsa Husada is a community service activity which is one of the obligations of Higher Education Institutions in implementing the Tri Dharma . The planned activity that will be implemented is reducing anxiety for pregnant women in the second and third trimesters through relaxing prenatal yoga, namely by providing steps and methods through education and practice. The activity was held in Goah Gumelar on Saturday 3 February 2024 and 25 participants attended.